О славянских соляных озерах - Леваковский, Иван Федорович; Леваковський, Іван Федорович (Харьков : В Университетской типографии, 1870)
The author describes the composition of the salt lakes, the physical and chemical properties of water in these lakes.
Keywords: Общество испытателей природы; Императорский Харьковский университет; Славянск; славянские соляные озера; соль поваренная